Utilization of Plastic Waste with The Ecobrick Method as an Effort to Reduce Plastic Waste in Sukarami Village Bengkulu City - Handayani, Dewi; Jelita; Muhammad Mukhlisin Alfaro; Nurul Annisa; Riesa Tirta Maladewi; Tri Septi; Winda Siptiani; Wovie Azizah; Yovi Sepriansyah (CV. Media Digital Publikasi Indonesia, 2025)
This community service aims to provide insight into knowledge and solutions that can be applied to reduce plastic waste and recycle it so that it becomes more useful to the community in Sukarami Village, Bengkulu City. The processing of plastic waste, can reduce the negative impact of environmental pollution and increase public awareness of the importance of protecting the surrounding environment. In this era of a creative economy that intensifies information and creativity by relying on ideas and knowledge, one of them is processing plastic waste into eco-bricks that can reduce plastic waste from environmental pollution and can improve the economy of the community in Sukarami Village, Bengkulu City. Bengkulu. Based on the results of these activities, the community is beginning to realize the importance and dangers of waste to the environment and health. In addition, the community was very enthusiastic about this activity and participated in it until it was completed.